PERTIMBANGAN KONSUMEN DALAM MEMBELI PRODUK GULA KELAPA DI KABUPATEN BANYUMAS - Dian Purnomo Jati; Suliyanto; weni Novandari (Jurnal Ekonomi dan Pembangunan, 2025)
The purpose of this study is to analyze the factors that influence consumer purchasing decisions on coconut sugar products in Banyumas regency. This research was conducted by using survey method to 100 respondents who are consumers of coconut sugar products in Banyumas Regency. This research uses binomial test to determine the factors that influence purchasing decision and Cochrans Q test to test attributes that influence significantly. Binomial test results show that the attributes of price, taste, color, aroma, durability, solubility, hygiene, benefits, ease of obtaining, and halal are the factors that consumers consider in buying coconut sugar in Banyumas regency. While based on Cochrans Q test, attributes that significantly influence the consideration of respondents are price, taste, aroma, color, cleanliness, easiness, and halal. It is hoped that the coconut sugar SMEs can develop marketing strategies relevant to these attributes.